Relationship between Physiological Profile Assessment (PPA) and Berg Balance Scale (BBS) scores in patients with stroke - Phirom, Kochaphan; Sanglah, Chorpaka; Sungkarat, Somporn (Journal of Associated Medical Sciences, 2017)
Background: Balance impairment and falls are a major problem and common in patients with stroke. Physiological Profile Assessment (PPA) was developed to identify physiological impairments underlying balance disorders and risk of falls in elderly people. The PPA has been used in patients with stroke but not as common as Berg Balance Scale (BBS). Objectives: To determine the relationship between PPA scores and BBS scores in patients with stroke. Materials and methods: Thirty patients with stroke (22 males, 8 females; mean age 61.07±12.34 years; mean post-stroke time 32.5±31.6 months) voluntarily participated in the study. The PPA and BBS were administered to all participants. Spearman correlation coefficient was used to determine the relationship between the PPA and BBS scores. The significance level was set at p<0.05. Results: Participants had mean PPA score of 2.88±1.56 points and mean BBS score of 42.80±12.38 points. Spearman correlation coefficient analysis revealed that the PPA scores had moderately negative correlation with the BBS scores (r = -0.475, p=0.008). Conclusion: Significant correlation between PPA and BBS scores could be due to the activities tested in the BBS require integration of physiological factors assessed in the PPA. As PPA provides information on physiological impairments underlying risk of falls, it is beneficial for planning interventions that are specific to patient’s problems. However, studies on psychometric property of PPA in patients with stroke are needed.